Transnacionalne socijalizacije, politike i institucije Evropske unije / Transnational Socialization, Politics and Institutions in EU - Pejanović, Mirko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
The text is a review of a book Transnational Socialization, Politics and Institutions in EU by Prof. Dr. Mile Lasić (HKD Napredak and Panevropska unija, 2016).